EFFECT OF BUYER-SUPPLIER RELATIONSHIPS ON PROCUREMENT PERFORMANCE: EVIDENCE FROM KENYAN SUPERMARKET - Korir Loice (European Scientific Journal, ESJ, 2015)
The purpose of this paper was to establish the effect of buyer-supplier relations on procurement performance. The study was informed by social exchange theory. This study employed explanatory research design. The target population was 112 procurement and sales managers drawn from thirty-four (34) supermarkets located in Nairobi County. Census technique was used. Data was obtained using structured questionnaires. Data was analyzed using descriptive statistics such as frequency, percentage, means, and standard deviation. In addition, Pearson correlation and multiple regression models were used to test linear relationship and hypothesis testing respectively. Study results showed that commitment, communication, cooperation and trust has a positive and significant effect on procurement performance. Hence, high levels of commitment, trust, communication and cooperation enhance sustainable competitive advantage hence improving the procurement performance. The study therefore recommends that there is need for firms to have a long term partnership with the major suppliers and aim at giving maximum attention to the relationship with suppliers so as to maintain it and enhance competitive advantage which will lead to improved procurement performance. There is also need for firms to have frequent and timely communication with suppliers and inform them of unforeseen challenges. Suppliers need to keep the promises made to the firm and offer credible information and keep the firm’s best interests in mind. Suppliers need to be responsible for the results of the industrialization and manufacturing process of the supplied part. It is also recommended that this study be replicated in different business sectors within the other regions.